Pengaruh Biaya Saluran Distribusi Dan Jumlah Tenaga Penjual Terhadap Volume Penjualan Pada Pt Teratai Widjaja - ., Sulistiono; Widjojo, Adi; Salman, Muhammad (Jurnal Ilmiah Manajemen Kesatuan, 2016)
The company's main objective is to enhance shareholder value and maximize shareholder wealth. One indicator is to increase the value of the company's profits. With the increase in earnings, the company can develop and maintain the company. Ways in which companies improve profits by increasing sales volume. To facilitate the flow of events from producers to consumers, company must make appropriate distribution channels that include quantity pricing and promotion. By choosing the right distribution channels to increase the company's sales volume. Distribution channels in order to achieve an appropriate target, it is necessary to charge the cost of distribution channels, as well as promotion and must be supported by a good sales person. With the appropriate sales person, the sales activities of the producer to the consumer can be achieved. The purposes of this study are (1) To determine the effect of cost distribution channel to sales volume (2) To determine the effect of the number of sales people to sales volume (3) To determine the effect of cost distribution channels and the number of sales people to sales volume. The results showed that the multiple linear regression equation is formed: Y = -135.3771 + 0.061. X1 + 0.330. X2. Sales volume is at the level of the ratio scale -135.3771. If the variable cost distribution channel (x1) increased scale ratio of 1 unit, then the cost of distribution channels will increase by 0.061 ratio scale, and with the assumption that the variables are considered constant number of sales people. If a variable number of sales people (x2) increased the ratio of 1 unit scale, the sales volume will increase by 0.330 scale ratio, and assuming that the number of sales people is considered constant. The coefficient of determination (R2) or variable R square on 0786 sales volume was 78.6%, which means the volume of sales are influenced by independent factors (cost distribution channels and the number of sales people). While the remaining 21.4% is influenced by other variables not included in this study. The correlation coefficient (R) is the sales volume on variable 0887 shows have a very close relationship between the independent factors (cost distribution channels and the number of sale speople) on sales volume, which is 88.7%.